Embedded flower pollination evolutionary programming based technique for voltage stability enhancement with distributed generation installation - Mansor N.N.; Shaaya S.A.; Musirin I.; Hannoon N.S.; Mohamed Z.; Zamani M.K.M. (World Academy of Research in Science and Engineering, 2023)
This paper presents the embedded flower pollination evolutionary programming-based technique for voltage stability enhancement with distributed generation installation. In this study, a new technique is developed which combines the element of flower pollination into the general evolutionary programming algorithm. The aim is to enhance the voltage stability in power system with the presence of distributed generation. The proposed technique was validated using the IEEE 33-Bus Distribution System. Results obtained from the study revealed that the proposed technique is better than EP in terms of optimizing the sizing of DG and location. 2019, World Academy of Research in Science and Engineering. All rights reserved.